DYN-NbC: A new routing scheme to maximize lifetime and throughput of WSNs - Khan, A.H. (Institute of Electrical and Electronics Engineers Inc., 2015)
In this paper, we present need-based clustering (NbC) with dynamic sink mobility (DYN-NbC) scheme for wireless sensor networks (WSNs). Our proposed scheme increases the stability period, network lifetime, and throughput of the WSN. The scheme incorporates dynamic sink mobility in a way that mobile sink (MS) moves from dense (in terms of number of nodes) regions towards sparse regions. Intelligently moving the sink to high density regions ensure maximum collection of data. As, more number of nodes (sensors) are able to send data directly to MS, therefore, significant amount of energy is saved in each particular round. However, there is a certain limitation to this approach. Nodes which are far from sink have to wait much for their turn. So, there are chances of buffer (node storage) overflow that is not desirable. To overcome this issue our scheme includes. Clustering (communication via CHs) becomes the part for those regions which are away from MS. Simulation results show that DYN-NbC outperforms the other two protocols D-LEACH and LEACH in terms of stability period, network lifetime, and network throughput. Â© 2015 IEEE.